Retail Loan Under Interest Rate Fluctuation in Nepal: Costumers Interest, Challenges and Managerial Solutions - Bhandari, Udbodh; Jaisi, Tilak; Devkota, Niranjan; Karki, Dipendra; Adhikari, Dipak Bahadur; Paudel, Udaya Raj; Parajuli, Seeprata (Journal of Asian Business Strategy, 2021)
Globally, interest rates play an important role in banking loans for all types of customers. In the present context, the banking sector is growing in Nepal. Banking sector is being popular for saving and retail loan purposes among the people of Kathmandu valley. Now a days, retail banking loan is being considered as one of the most innovative financial services provided by the various banks and financial institutions. This paper presents dimensional analysis of retail loan under interest rate fluctuation in Nepal. Respondents for the study were chosen using convenience sampling and random sampling methods. Convenience sampling was primarily used to select bank employees, while random sampling was used to select bank customers. The structured questionnaire, expert opinion, and pre-test interview are research instruments used in the study to collect data from bank employees and customers of Karhmandu valley. This paper reveals that youth and highly educated people are more attracted towards the retail banking products. Most of the respondents focus that there is a challenge in retail loan.